Fecal Microbiome Does Not Represent Whole Gut Microbiome - Ji-Seon Ahn; Enkhchimeg Lkhagva; Sunjun Jung; Hyeon-Jin Kim; Hea-Jong Chung; Seong-Tshool Hong (Cellular Microbiology)
The current gut microbiome research relies on the fecal microbiome under the assumption that the fecal microbiome represents the microbiome of the entire gastrointestinal (GI) tract. However, there have been growing concerns about using feces as a proxy to study the gut microbiome. Here, we comprehensively analyzed the composition of microbiome and metabolites in the feces and at 14 different locations of GI tracts of genetically homogenous sibling pigs to evaluate the validity of using feces as a proxy to the whole gut microbiome. The composition of intestinal microbes constituting the gut microbiome at each intestinal content and feces and their metabolic compositions were thoroughly investigated through metagenome sequencing and an ultraperformance LC-MS/MS, respectively. The fluctuation in the composition of the microbiome in the stomach and the small intestine became stabilized from the large intestine to feces and was able to be categorized into 3 groups. The taxonomic α-diversities measured by ACE (abundance-based coverage estimator) richness and Shannon diversity indicated that the microbiome in the large intestine was much more diverse than those of the small intestine and feces. The highly independent intestinal microbes in the stomach and the small intestine became flourished in the large intestine and converged into a community with tightly connected networks. β-Diversity analyses by NMDS plots, PCA, and unsupervised hierarchical clustering all showed that the diversities of microbiome compositions were lowest in feces while highest in the large intestine. In accordance with fluctuation of the composition of gut microbiome along with the GI tract, the metabolic composition also completely differed in a location-specific manner along with the GI tract. Comparative analysis of the fecal microbiome and metabolites with those of the whole GI tract indicated that fecal microbiome is insufficient to represent the whole gut microbiome.